2010
DOI: 10.3174/ajnr.a1922
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cerebrovascular Reactivity by Blood Oxygen Level–Dependent MR Imaging and Correlation with Conventional Angiography in Patients with Moyamoya Disease

Abstract: BACKGROUND AND PURPOSE: BOLD MR imaging combined with a technique for precision control of end-tidal pCO 2 was used to produce quantitative maps of CVR in patients with Moyamoya disease. The technique was validated against measures of disease severity by using conventional angiography; it then was used to study the relationship between CVR, vascular steal, and disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 7 publications
1
54
0
1
Order By: Relevance
“…[11][12][13] The breath-hold (BH) technique offers a simpler alternative that is easier to implement in the clinical setting and yet can produce similar increases in arterial CO 2 levels and resultant similarly useful BOLD CVR maps as those achieved by using gas-inhalation techniques. 14 This technique involves short-duration BHs, typically in the range of 10 -30 seconds, which alternate with periods of normal breathing.…”
Section: The Breath-hold Cerebrovascular Reactivity Mapping Techniquementioning
confidence: 99%
“…[11][12][13] The breath-hold (BH) technique offers a simpler alternative that is easier to implement in the clinical setting and yet can produce similar increases in arterial CO 2 levels and resultant similarly useful BOLD CVR maps as those achieved by using gas-inhalation techniques. 14 This technique involves short-duration BHs, typically in the range of 10 -30 seconds, which alternate with periods of normal breathing.…”
Section: The Breath-hold Cerebrovascular Reactivity Mapping Techniquementioning
confidence: 99%
“…10 The physiologic origins of a negative BOLD response are known to occur in and around capillaries and draining veins from decreases in blood oxygenation, which could occur from reductions in CBF (vascular steal), increases in CBV (autoregulation), or upregulation of CMRO 2 ( Figure 1). It should also be noted that while changes in venous CBV are generally smaller in magnitude than changes in arterial CBV, such changes influence BOLD substantially owing to the larger fraction of deoxyhemoglobin in veins.…”
Section: Origins Of Negative Blood Oxygenation Level-dependent Cerebrmentioning
confidence: 99%
“…Such negative BOLD effects have been shown to correlate inversely with cortical thickness and directly with IC vascular disease severity. 10 The mechanism underlying negative BOLD responses, however, is controversial. Occlusion models in animals have demonstrated that hypercarbia does not change CBF in ischemic brain 11,12 and in subacute human stroke patients, it has been demonstrated that CBF response to hypercarbia is heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…24 Cerebrovascular reactivity as measured by blood oxygen level-dependent MRI has also been shown to have a direct correlation with impaired vascular supply as measured by modified Suzuki score on angiography. 25 Quantitative MR angiography with NOVA software can show actual blood flow across large intracranial vessels and also flow across the superficial temporal artery after revascularization. 26 In our practice, xenon CT (without and with acetazolamide) has provided an excellent quantitative method of assessing CBF and hemodynamic reserve with good spatial resolution; however, it is not currently approved by the Food and Drug Administration and can only be used on an Institutional Review Board-approved protocol.…”
Section: Imagingmentioning
confidence: 99%